The trichloroethylene metabolite S-(1, 2-dichlorovinyl)-L-cysteine induces progressive mitochondrial dysfunction in HTR-8/SVneo trophoblasts. (1st November 2019) - Elkin, Elana R.; Bridges, Dave; Loch-Caruso, Rita
Graphical abstract: Highlights: DCVC decreased mitochondrial content in HTR-8/SVneo placental trophoblasts. DCVC induced adaptive and subsequently pathogenic mitochondrial perturbations. (±)-α-tocopherol attenuated DCVC-induced mitochondrial membrane depolarization. (±)-α-tocopherol failed to attenuate DCVC-induced oxygen consumption perturbations. Mitochondria are prominent intracellular targets of DCVC injury in placental cells. Abstract: Trichloroethylene is an industrial solvent and common environmental pollutant. Despite efforts to ban trichloroethylene, its availability and usage persist globally, constituting a hazard to human health. Recent studies reported associations between maternal trichloroethylene exposure and increased risk for low birth weight. Despite these associations, the toxicological mechanism underlying trichloroethylene adverse effects on pregnancy remains largely unknown. The trichloroethylene metabolite S -(1, 2-dichlorovinyl)-L-cysteine (DCVC) induces mitochondrial-mediated apoptosis in a trophoblast cell line. To gain further understanding of mitochondrial-mediated DCVC placental toxicity, this study investigated the effects of DCVC exposure on mitochondrial function using non-cytolethal concentrations in placental cells. Human trophoblasts, HTR-8/SVneo, were exposed in vitro to a maximum of 20 μM DCVC for up to 12 h. Cell-based oxygen consumption and extracellular acidification assays were used to evaluate key aspects of mitochondrial function. Following 6 h of exposure to 20 μM DCVC, elevated oxygen consumption, mitochondrial proton leak and sustained energy coupling deficiency were observed. Similarly, 12 h of exposure to 20 μM DCVC decreased mitochondrial-dependent basal, ATP-linked and maximum oxygen consumption rates. Using the fluorochrome TMRE, dissipation of mitochondrial membrane potential was detected after a 12-h exposure to 20 μM DCVC, and (±)-α-tocopherol, a known suppressor of lipid peroxidation, attenuated DCVC-stimulated mitochondrial membrane depolarization but failed to rescue oxygen consumption perturbations. Together, these results suggest that DCVC caused progressive mitochondrial dysfunction, resulting in lipid peroxidation-associated mitochondrial membrane depolarization. Our findings contribute to the biological plausibility of DCVC-induced placental impairment and provide new insights into the role of the mitochondria in DCVC-induced toxicity.